2009
DOI: 10.1093/heapol/czp017
|View full text |Cite
|
Sign up to set email alerts
|

Providing information on pregnancy complications during antenatal visits: unmet educational needs in sub-Saharan Africa

Abstract: There is a high level of unmet need for information on pregnancy complications in sub-Saharan Africa, particularly among those who face significant barriers to accessing care if complications occur. Educational interventions are critical to safe motherhood initiatives; health providers must fully use the educational opportunity in antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
68
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 21 publications
14
68
1
2
Order By: Relevance
“…Knowledge of maternal and newborn danger signs is reported to promote active preparation for the delivery of the baby and quicken the decision-making process with regard to accessing appropriate care [1113]. Hence, birth preparedness interventions help to address key bottlenecks to delays in deciding to seek care and reaching the place of care [6–9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of maternal and newborn danger signs is reported to promote active preparation for the delivery of the baby and quicken the decision-making process with regard to accessing appropriate care [1113]. Hence, birth preparedness interventions help to address key bottlenecks to delays in deciding to seek care and reaching the place of care [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, birth preparedness interventions help to address key bottlenecks to delays in deciding to seek care and reaching the place of care [6–9]. Comprehensive birth preparedness therefore enhances the ability of women, their partners, and families to engage in safe motherhood initiatives [10,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that 51(8.1%) who experienced obstetric danger signs 44(7.0%) had Good practice seek medical care when they faced problem. A study done in Indonesia, revealed that among the pregnant women who attended ANC, 36.6% of the respondents gave correct answers to a question on common practice such as, it is necessary to go to the hospital when severe headache or vision problems happen in pregnancy [11][12][13][14]. The difference might be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…It comprised of five sections: Section A -Demographic Data Inventory; Section B: Sources of Information on Antenatal Care -13 items; Section C: Information Seeking Needs -12 items; Section D: Perceived Problems Inhibiting Information Seeking Needs -10 items; Section E: Information Seeking Types -10 items. The levels of information-need and information-seeking were categorized as high (35-50), moderate/average (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and Low (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Maximum attainable score was 50.…”
Section: Instrument For Data Collectionmentioning
confidence: 99%